The Effect of Students Helping Students (SHS) Techniques in Improving Reading Comprehension in the New Normal Era - Muhammad Rafiq; Ardiansah Ardiansah (International Journal of Educational Development and Innovation, 2021)
This study aims to determine the effect of the Students Helping Students (SHS) technique in improving students' reading comprehension of English texts in the New Normal Era. This research is a classroom action research in class VIIIA SMPN 3 Pitumpanua Wajo district. The data in this study are class observations, test results, and the results of distributing questionnaires. Class observations were carried out during the implementation of the action, while the tests were the results of the pre-test before the action and the results of the post-test after the action, while the distribution of the questionnaire was to see the students' attitudes towards the application of the SHS technique in learning to read. There are two ways in implementing learning in the new normal era, namely online classes and offline classes by complying with health protocols. During the implementation of the action of implementing SHS in learning, it showed an effect on increasing learning outcomes, increasing student motivation, good group cooperation, increasing vocabulary and increasing students' abilities and courage in expressing opinions. The test results showed that the post-test results were higher than the pre-test results, indicating that there was a significant increase. With the application of this SHS technique, students show their positive attitude which is indicated by responses through a questionnaire. It can be assumed that the application of the SHS technique in learning reading comprehension in junior high school is very effective and has an influence on improving student learning outcomes.